Life prediction of thermal barrier coating considering degradation and thermal fatigue - Song, Hyunwoo; Kim, Yongseok; Lee, Jeong-Min; Yun, Junghan; Kim, Dae-Jin; Koo, Jae-Mean; Seok, Chang-Sung (International journal of precision engineering and manufacturing, 2016)
A thermal barrier coating (TBC) is used to protect gas turbine components from extreme environments. Typically, the TBC system consists of two parts: a ceramic top coat and metallic bond coat. Thus, the TBC system is exposed to thermal fatigue owing to the mismatch between the thermal expansions of the ceramic top coat and metallic bond coat. The durability of the TBC decreases with repeated thermal fatigue and degradation under high-temperature conditions, which can eventually result in failure. Therefore, the life of the TBC should be predicted while considering degradation and thermal fatigue. In this study, TBC specimens were produced under different degradation and thermal fatigue conditions, and the bond test was performed on these specimens. Based on the bond test results, the life of the TBC was predicted according to degradation and thermal fatigue.